Simultaneous growth of monolayer graphene on Ni–Cu bimetallic catalyst by atmospheric pressure CVD process. Issue 47 (26th April 2016) - Seah, Choon-Ming; Vigolo, Brigitte; Chai, Siang-Piao; Ichikawa, Satoshi; Gleize, Jérôme; Ghanbaja, Jaafar; Mohamed, Abdul Rahman
Abstract : CVD is the most efficient way to produce wafer scale monolayer graphene. Abstract : CVD is the most efficient way to produce wafer scale monolayer graphene. Although Ni and Cu are widely reported catalysts for monolayer graphene formation, but both Ni and Cu are requiring different extreme conditions to grow graphene in single layer. Here, we show that monolayer graphene could be grown simultaneously on polycrystalline Ni and Cu under single atmospheric pressure CVD for the first time. Our catalyst system combines carbon solubility divergence between the two catalysts to limit the exposure to the carbon source. Structure and quality of the grown graphene were characterized by HRTEM and Raman spectroscopy mapping. The growth mechanism shows that the role of grain boundaries is crucial for carbon diffusion tuning. The results show that free-standing high-quality monolayer graphene can be produced in a controlled and simple way with an affordable catalyst system.